Electronic information systems and their role in developing administrative work from the point of view of administrators in the College of Education at King Saud University - Barayan, Adel Salem; Almanie, Abdullah Mohammed (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the degree of administrators’ satisfaction in the College of Education at King Saud University with electronic information systems, and to identify the degree of their use of them, as well as to identify the role of electronic systems in developing administrative work, and to know this, the researchers prepared a questionnaire consists of (22) items to be answered by the college administrators, the study was applied in the first semester of the year 2021, and the study reached the following results: that the degree of administrators’ satisfaction with the electronic information systems came to a high degree, and that the degree of their use of electronic information systems was high, as well as the study found that the degree of The college administrators' satisfaction with the technical services provided to electronic information systems was high, and the study concluded that electronic information systems contribute to developing administrative work and accelerating the completion of transactions.In light of this, the study recommended continuing to improve and develop electronic and academic information systems according to the suggestions and requirements of the beneficiaries from administrators, academics and students, and to increase the effectiveness of integration and interdependence between university systems by holding continuous meetings with administrators, faculty members and students to identify development suggestions and overcome existing problems, and design Specialized training programs for the administrative staff to acquire skills in dealing with electronic systems and how to develop them and solve their technical problems with high efficiency.
Keywords: Information systems; management information systems; electronic management; developing work; College of Education